Activating the Vertical City: An Office Building in Chengdu, China - Tan, Jujie (My University, 2019)
In recent years, China has built more skyscrapers than any other country has in the world. The skyscrapers create an overpowering “vertical city” that could be anywhere. These tall structures stack all their major functions such as commercial space, workspace and residential space in a single tower that have become major consumers of energy and power. These tall buildings fail to address the problems of the social well-being and physical health of the workers. This thesis proposes that tall buildings in major Chinese cities need to be more active and connect to the neighborhood. The design creates separate towers with a vertical void in the middle to provide space for the needed facilities but at the same time activated the highrise buildings. The aim is to really think about the relationship between the public and the private in order to make a comfortable and active workspace.
Thesis (Master's)--University of Washington, 2018
Keywords: Architecture; Architecture